Where authority, speech acts and modality meet: A pragmatic analysis of the trial record of King Charles I - Nakayasu, Minako; Shiina, Michi (LingBaW. Linguistics Beyond and Within, 2024)
This paper investigates how speakers perform speech acts coordinating with modality in the flux of power in Early Modern courtroom interactions along the lines of historical pragmatics. The text used for analysis is the trial record of King Charles I in the Sociopragmatic corpus, in which the King was put on trial on the charge of high treason. First, examination of vocatives, noun phrases, verb phrases and grammatical subjects shows who has the authoritative power in interaction, the Lord President (the judge) or the King (the defendant). Next, quantitative and qualitative analyses of speech acts performed with the aid of modals demonstrate the tendency that the speech acts performed by the Lord President are highly relevant to deontic modality, while those performed by the King are closely related to dynamic modality. This reflects which authority the two parties depend upon: authority of the Court, and authority of the King/Kingdom, respectively. The analysis of authority, speech acts and modality reveals that the King becomes less authoritative as the trial proceeds, particularly after the sentence has been pronounced. On the other hand, the authority of the Court, which is manifested in the Lord President’s speech, stays the same throughout the course of the trial. To summarise, this research shows how the judge and the defendant interacted with each other in a fluctuating power relationship in the courtroom, at the interfaces between authority, speech acts and modality, where their viewpoints and attitudes are reflected.